Dasar Pemahaman Keislaman Jaringan Islam Liberal (Jil) - Husaen Pinang (IAI DDI POLEWALI MANDAR, 2017)
Certainly the existence of Islamic Liberal Network in Islamic consideration primarily has made pro and contra around the Islamic brainware, it can be seen in social media, some book and even in public discuss, it makes this community sometimes in considered as deviate ideology. Based on pro and contra itself the writer is interested to explain about the understanding of Islamic according to this community in a proper discourse. Using descriptive analyse method the writer has found that basicly the Islamic understanding of this community based on liberal thoughts, understanding the religion contextually and putting ethical religion forward not even on the text an sich. The purpose of this research to show that every new patten of understanding in mainstream disposed to be faulted and lost. That is what happened in Islamic network, it is becaused of uknowing toward the community which absolutely no need fault and lost